Factors Affecting Financial Behaviors:: Studies in Students Who Do Venture Creation - Jean Adriani (Universitas Ciputra Surabaya, 2021)
This study was conducted to determine the effect of financial knowledge, financial attitude, locus of control, risk tolerance, motivation, and mental accounting on financial behavior. The population was 168 students majoring in International Business Management at Universitas Ciputra Surabaya. The characteristics of the respondents are students who are in the 6th semester and above at the time of taking the sampling with purposive sampling method. The data obtained were analyzed using Partial Least Square (PLS). The result shows that the factors of financial knowledge, locus of control, motivation, have no effect on financial behavior. While the factors of financial attitude, risk tolerance, and mental accounting have an effect on financial behavior.